The internal values of akhlak in Kaba Si Sabariah for educational character development: (Nilai akhlak dalam Kaba Si Sabariah bagi pembangunan sahsiah Pendidikan) (RENTAS: Jurnal Bahasa, Sastera dan Budaya, 2024)
The purpose of this research is to identify the akhlaq (أخلاق‎) values in the literary work. The method used in this study was content analysis, which involved collecting data from Kaba Si Sabariah and analyzing the akhlaq values within it. The result showed eight akhlaq in Kaba. These akhlaq values can be used as teaching material to support the internalization of the dimensions of faithfulness, devotion to the one almighty God, and possession of noble character, one of the six dimensions of the Pancasila student profile. In teaching akhlaq, studying literary works such as Kaba Si Sabariah is highly relevant and can help reinforce the teaching of akhlaq values because literary works have a strong appeal for conveying these messages. Therefore, this study contributes to developing akhlaq education through literary works as a valuable educational resource.